2023
DOI: 10.3390/ijms24119577
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative and Neurodevelopmental Diseases and the Gut-Brain Axis: The Potential of Therapeutic Targeting of the Microbiome

Abstract: The human gut microbiome contains the largest number of bacteria in the body and has the potential to greatly influence metabolism, not only locally but also systemically. There is an established link between a healthy, balanced, and diverse microbiome and overall health. When the gut microbiome becomes unbalanced (dysbiosis) through dietary changes, medication use, lifestyle choices, environmental factors, and ageing, this has a profound effect on our health and is linked to many diseases, including lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 516 publications
0
32
0
Order By: Relevance
“…Accumulated evidence indicates that the gut microbiome plays a critical role in the development of neurodegenerative and neurological diseases 16 . We have previously shown that in comparison to WT mice, the gut microbiota composition of Cln2 R207X mice is significantly altered 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Accumulated evidence indicates that the gut microbiome plays a critical role in the development of neurodegenerative and neurological diseases 16 . We have previously shown that in comparison to WT mice, the gut microbiota composition of Cln2 R207X mice is significantly altered 17 .…”
Section: Resultsmentioning
confidence: 99%
“…The Western diet has sped up changes in the human microbiome. Highly processed foods, animal products, and sugars alter the microbiome to cause intestinal inflammation [ 7 ].…”
Section: Causes Of Dysbiosismentioning
confidence: 99%
“…A link has been found between the composition of the intestinal microbiota and several diseases and symptoms, such as pain, cognitive function, and neurodegenerative diseases [ 1 , 2 , 3 , 4 , 5 , 6 ]. This link suggests not only that the gut microbiota composition can serve as the basis to make an early diagnosis of neurodegenerative and neurodevelopmental diseases but also that modifying the gut microbiome to influence the microbiome–gut–brain axis might present a therapeutic target for these diseases [ 7 ]. The composition, density, and diversity of our individual microbiomes are dynamic and affected by multiple factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects of PBM in reducing inflammation and edema, restoring blood flow, improving tissue healing, and inducing analgesia have been widely demonstrated in humans [ 16 , 17 , 18 ]. Moreover, there is also growing evidence that PBM may influence the microbiome [ 19 , 20 , 21 , 22 , 23 , 24 ]. Interestingly, Bicknell and colleagues demonstrated that PBM delivered to the abdomen of mice produced a significant change in the gut microbiome and, in humans, they observed a change in the microbiome in Parkinson patients after PBM treatment [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%